القدس عند النصارى دراسة لتغيير الموقف النصراني من الإفراط إلى التفريط Jerusalem from an Obsession to Indifference: A Christian Perspective Al-Quds disisi Penganut Kristian: Kajian tentang Perubahan Pendirian Melampau Penganutnya kepada Pengabaian - Mustapha, Maziah; Muhammad Amin Said, Zana (IIUM, 2017)
The aim of this study is to explore and investigate the pivotal position occupied by the city of Jerusalem (al-Quds) in Christendom. Very precisely, the study will investigate this city in the context of the Christian doctrine ever since the institutionalization of the religion till to this day. The researcher is pretty much interested in studying the reasons behind the overflowing love and the dissipation of love over this city by the followers of Christianity. The researcher employed the inductive, historical, and analytical methods in analyzing the authentic data found both in Christianity and Islam. The researcher has come to know that once al-Quds had a great significance for the Christians from the religious and political perspectives.Christians showed great enthusiasm for the city up until the 16th century. Later they withdraw their right to this city, leaving it to the Jews to claim ownership to it till today. The Protestant sect was the first among the various denominations in Christendom which withdrew the right over the city of Jerusalem. In a way, this research is important in studying the underlying factors that caused the Christians to handover the claim over Jerusalem to the Jews.